2016
DOI: 10.1038/srep21915
|View full text |Cite
|
Sign up to set email alerts
|

The role of photo-electric properties of silk cocoon membrane in pupal metamorphosis: A natural solar cell

Abstract: Silkworm metamorphosis is governed by the intrinsic and extrinsic factors. One key intrinsic factor is the temporal electrical firing of the neuro-secretory cells of the dormant pupae residing inside the silk cocoon membrane (SCM). Extrinsic factors are environmental like temperature, humidity and light. The firing pattern of the cells is a function of the environmental factors that eventually controls the pupal development. How does the nervous organization of the dormant pupae sense the environment even whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…The recent experiments on the most abundant natural fibers from insect, animal and plant kingdom 22 26 viz., silk cocoon ( Bombyx mori , Antheraea mylitta ), human hair, jute and corn-silk (obtained from the corn cob of the maize plant) show that at optimum moisture, temperature and light conditions, these fibers exhibit thermoelectric, photo-electric and magnetic properties 1 , 2 , 27 , 28 . However, the nature of charge carriers and the effect of water (if any) on the charge transport properties of these fibers, have not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…The recent experiments on the most abundant natural fibers from insect, animal and plant kingdom 22 26 viz., silk cocoon ( Bombyx mori , Antheraea mylitta ), human hair, jute and corn-silk (obtained from the corn cob of the maize plant) show that at optimum moisture, temperature and light conditions, these fibers exhibit thermoelectric, photo-electric and magnetic properties 1 , 2 , 27 , 28 . However, the nature of charge carriers and the effect of water (if any) on the charge transport properties of these fibers, have not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…Successful metamorphosis of dormant pupae to an adult moth is function of temperature, humidity, light, UV protection, water proofing, gaseous balance and physical protection from the predators 1 2 3 4 5 6 7 8 9 10 11 12 . To meet these requirements, nature evolved a ‘robust growth incubator’ in the form of ‘silk cocoon’, which is equipped with moisture, heat and light sensor 1 2 3 5 . Studies have confirmed that SCM converts photons, especially in UV range, to generate electricity 1 .…”
mentioning
confidence: 99%
“…To meet these requirements, nature evolved a ‘robust growth incubator’ in the form of ‘silk cocoon’, which is equipped with moisture, heat and light sensor 1 2 3 5 . Studies have confirmed that SCM converts photons, especially in UV range, to generate electricity 1 . Similarly in presence of moisture, heat energy is converted into electrical signals by SCM 2 3 .…”
mentioning
confidence: 99%
See 2 more Smart Citations